If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xy + -6xyz = 3 Solving 3xy + -6xyz = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Reorder the terms: -3 + 3xy + -6xyz = 3 + -3 Combine like terms: 3 + -3 = 0 -3 + 3xy + -6xyz = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-1 + xy + -2xyz) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-1 + xy + -2xyz)' equal to zero and attempt to solve: Simplifying -1 + xy + -2xyz = 0 Solving -1 + xy + -2xyz = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + xy + 1 + -2xyz = 0 + 1 Reorder the terms: -1 + 1 + xy + -2xyz = 0 + 1 Combine like terms: -1 + 1 = 0 0 + xy + -2xyz = 0 + 1 xy + -2xyz = 0 + 1 Combine like terms: 0 + 1 = 1 xy + -2xyz = 1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 156=(6w-9) | | 2z^2=30+7z | | 6ab-8bc=4bd | | 5u+2v= | | -9d^2=-405 | | 2xy-xz=4 | | 8*8=8 | | 11/4(5/3x-7/4) | | 8*8=111 | | 8*5=70 | | x/-3+12 | | 6u+v=18 | | (2+4)*5+10-18+7+5*(7+1)+4*0= | | 2t/3=4/9 | | 6c+3u=36 | | (3b-c-4)=2 | | 81x-8=1 | | 81x-=1 | | 4.6w+0.19=5539 | | 4x-y+8=2 | | 26=-3x+5 | | (4x-y+8)=2 | | 3x^4+8x^3-15x-40=0 | | 3(x+1)=y | | .018c=36 | | f(x)=(x^2+4x+4)-3 | | .4y=48 | | .06b=24 | | Y-x+1=1 | | .002t=6 | | .7a=490 | | -73=5n+78 |